The Effect Of Auditor Reputation, Audit Committee And Audit Tenure On Audit Quality (Study on Consumer Non-Cyclical Companies Listed on The Indonesia Stock Exchange (IDX) in 2020-2023) - Hani Anggia Khairin; Galuh Tresna Murti (Telkom University, 2025)
Audit quality is the ability of an auditor to find material misstatements and disclose these errors, where in carrying out their duties the auditor is guided by relevant auditing standards and codes of ethics for public accountants. This study aims to determine the effect of auditor reputation, audit committee and audit tenure on audit quality in primary consumer goods companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. Populace concentrate on comprises of essential shopper merchandise organizations recorded on the IDX somewhere in the range of 2020 and 2023. A quantitative methodology, using optional information, was utilized to test the examination speculations. IBM SPSS Statistics version 25 was used for the data analysis. A purposive sample of 37 key consumer goods companies that were listed on the IDX between the years 2020 and 2023 provided 148 data points for analysis. In this study, descriptive statistics and strategic regression were used. The findings, with a significant p-value of 0.001 (less than 0.05), indicate that auditor tenure, audit committee membership, and auditor reputation collectively influence audit quality. When examined individually, each factor auditor tenure, audit committee membership, and auditor reputationalso affects audit quality. These insights can assist stakeholders in focusing on factors that enhance audit quality, leading to more informed and objective decisionmaking.